THE LANGUAGE ATTITUDE OF THE FARMERS OF ALAHAN PANJANG TOWARD THEIR INDONESIAN - Murdelvia Putri; Hamzah Hamzah (Universitas Negeri Padang, 2016)
This paper aims to identify the attitudes of farmers towards Indonesian language in Alahan Panjang and factors of what makes the farmers in Alahan Panjang had an attitude. This research was descriptive quantitative field that describes the attitude of farmer opinion against the phenomenon of language attitude occurred. This attitude derived from the distribution of research questionnaires and interviews to farmers in Alahan Panjang which has business associates in Indonesian language. Their age restrictions on farmers is between 30-55 years. The results showed 92 out of a total of 100 farmers in Alahan Panjang were used as participants in the study showed a negative attitude towards Indonesian. They are not proud and do not want to use the Indonesian language in which they are located. There are several factors that cause these farmers Indonesian negative towards such social factors, a situation the use of language, gender, prestige, and cultural factors. The results of this study prove that farmers in Alahan Panjang do not want to use the Indonesian language in communication. They will only use the Indonesian language when communicating with people who only understand Indonesian.